Academic versus non-academic neurosurgeons in China: a national cross-sectional study on workload, burnout and engagement. Issue 10 (16th October 2019) - Yu, Jinli; Gao, Jiming; Chen, Junyan; Sun, Yirui
Abstract : Objectives: Chinese neurosurgery has made great progress during the past decades; yet, little is known about the working status of neurosurgeons. This study aimed to evaluate the difference between academic and non-academic neurosurgeons, focusing on their professional burnout, job satisfaction and work engagement. Design: Cross-sectional nationwide survey. Study setting: The survey was conducted in China between 2017 and 2018. Participants: A total number of 823 academic neurosurgeons and 379 non-academic neurosurgeons participated in this study. Outcome measures: Professional burnout, job satisfaction and work engagement were assessed using the Maslach Burnout Inventory, the Job Descriptive Index and the Utrecht Work Engagement Scale, respectively. Results: The majority of respondents were male (92.93%), less than 45 years old (85.27%) and married (79.53%). Chinese neurosurgeons worked 63.91±11.04 hours per week, and approximately 45% experienced burnout. Compared with non-academic respondents, academic neurosurgeons had longer working hours (p<0.01), higher income (p<0.01) and were less willing to get married (p<0.01). In addition, they showed a lower degree of burnout (p<0.01), a higher level of job satisfaction (p<0.01) and were more enthusiastic at work (p=0.015). Multivariate regression analyses indicated that divorced (OR 7.02, 95% CI 2.37 to 15.08) and workplace violence (OR 1.52, 95% CI 1.18 to 2.24) were associated with burnout for both academic and non-academic respondents. Long working hours (≥71 hours per week) and low annual income (<1 00 000 RMB) were risk factors for burnout among academic neurosurgeons. For non-academic neurosurgical surgeons (age 36–45 years), working as attending doctors, serving in public hospitals and having the first house-living child were all closely related to the incidence of burnout. Conclusion: Chinese neurosurgeons are under significant stress particularly for the non-academic neurosurgeons. Offering better opportunities for training, promotion, higher income and safer working environments could be solutions to relieve burnout and improve career satisfaction and engagement. Trial registration number: ChiCTR1800014762. This article is not linked to a clinical trial.